A biomimetic approach for enhancing adhesion and osteogenic differentiation of adipose-derived stem cells on poly(butylene succinate) composites with bioactive ceramics and glasses. (February 2017) - Nerantzaki, Maria; Koliakou, Iro; Kaloyianni, Martha G.; Koumentakou, Ioanna; Siska, Evangelia; Diamanti, Eleftheria; Karakassides, Michael A.; Boccaccini, Aldo R.; Bikiaris, Dimitrios N.
Graphical abstract: Highlights: PBSu nanocomposites were prepared by in situ polymerisation. Both additives accelerating the in vitro biodegradability of PBSu. Hydroxyapatite formation was found in all PBSu composite surfaces. Biocomposites induces osteogenic differentiation of rat Adipose Stem Cells. Abstract: The great potential application of poly(butylene succinate) (PBSu) as a novel biomaterial has not yet been realized, mainly owing to its insufficient bioactivity and low mechanical properties, which compromise the in vivo efficacy. Our strategy is based on the hypothesis that the incorporation of bioactive ceramics with similar microstructure to native bone structure into PBSu improves its bioactivity and affects new bone growth enhancing bone formation. Bioactive CaO–MgO–SiO2 –Na2 O–P2 O5 –CaF2 glass microparticles and fibrous hydroxyapatite nanoparticles were successfully synthesized and the resulting powders were characterized using different techniques. Afterwards, PBSu nanocomposites containing 2.5 wt% of micro-Bioglass (mBG), nano-hydroxyapatite (nHA) or mBG-nHA were prepared via in situ polymerization and were studied thoroughly in terms of their physicochemical and biological properties. We show here that our strategy was effective in accelerating the in vitro biodegradability of PBSu, in enhancing apatite formation in contact with simulated body fluid (SBF), while inducing cytocompatibility and osteogenic differentiation of rat Adipose Stem Cells (rASCs).